KEANEKARAGAMAN FLORA CAGAR ALAM NUSABARONG, JEMBER - J AWA TIMUR - Partomihardjo, Tukirin; Ismail, Ismail (Research Center for Biology-Indonesian Institute of Sciences, 2008)
Flora of Nusa Barong Nature Reserve, Jember-East Java, was intensively surveyed in 2005. At least 357 specimens consist of 282 species belonging to 232 genera and 88 families have been collected during the survey. Those are includes four species of Pterydophytes and 278 species of Spermatophytes. Among them there were three protected species Corypha utan, Excoecaria agalloca and Protium javanicum. Based on the IUCN categorization status, there were five species under threatened condition, i.e.Agalia edulis (LR/nt), Casearia flavovirens (VU.Bl+2c), Cycas rumphii (NT decreasing), Intsia bijuga and Intsia palembanica,both under VU.Al.cd.The natural population of these last two species was drastically decreasing due to the international trade. Most of the species recognized as new records for the island since there was no complete flora record of the area. Further studies are needed to gain more complete biodiversity information of small island ecosystem.